Anthropometrical features of cerebral palsy football players according to their impairment classification and playing position - Borges, Mariane; de Faria, Fernando Rosch; Buratti, Jéssica Reis; Vieira, Andreia Bauermann [UNESP]; de Sá, Karina Santos Guedes; Vieira, Ivaldo Brandão; Nogueira, Claudio Diehl; E Silva, Anselmo de Athayde Costa; Gorla, José Irineu (FapUNIFESP (SciELO), 2024)
CP football is played by male athletes with cerebral palsy, with rules similar to soccer, with some adaptations, but with the same demands for results and motor performance. Therefore, the objective of this study was to identify and analyze the anthropometric profile, body composition, somatotype, and motor performance of CP Football athletes, according to the impairment topography, sport class and game position. Thirty-seven athletes from the Brazilian CP football team participated in the study, who had body mass, height, circumference, bone diameters, skinfold thickness, and agility, speed and aerobic capacity VO2max tests. The motor performance of CP football athletes, in speed and aerobic capacity tests were significantly different (p<0.05) according to the impairment topography. Significant correlations were found between the impairment topography and sport classes for the variable’s agility (r= 0.39 and r=-0.40), 30m speed (r= 0.50 and r=-0.48) and the aerobic capacity VO2 max (r=-0.39 and r= 0.62). This study presents indications that the anthropometric, body composition and somatotype variables do not differ according to the impairment topography, functional class and game position in CP football athletes. Such findings can be guiding for the teams of the modality, as they differ from the conventional sport.
Características antropométricas de jogadores de futebol com paralisia cerebral de acordo com sua classificação funcional e posição de jogo
Keywords: Anthropometry; Cerebral palsy; Para-athletes